Salmon lice (Lepeophtheirus salmonis) control method effectiveness in Atlantic salmon (Salmo salar) aquaculture. A systematic literature review. - Cerbule, Kristine (UiT The Arctic University of Norway, 2018)
Background: Salmon lice (Lepeophtheirus salmonis) is an increasing limiting factor of Atlantic salmon (Salmo salar) aquaculture development in Northern Hemisphere. Different types of treatments have been tested and used to control lice on farmed Atlantic salmon with varying results. The aim of this systematic review is to examine effectiveness expressed as the reduction of the number of lice and associated negative effects to fish health and welfare (Atlantic salmon and cleaner fish, if used) for three types of methods – chemical treatment, cleaner fish use and warm water treatment. Methods: a systematic literature review was used to gather and analyse data related to each type of method reported in peer-reviewed documents. Results: After applying inclusion criteria, 62 of 782 documents of two scientific databases combined were further analysed. Most of the documents described chemical treatment which showed decreasing effectiveness combined with increasing concentrations due to the significant development of resistance. Documents describing the use of cleaner fish showed effectiveness towards salmon lice in all studies with little or no negative associated effects, and did not show a decreased effectiveness over time. The lack of data related to warm water treatment did not allow to assess the effectiveness of this method. Conclusions: Due to the development of resistance in lice selected by chemical treatments, those methods cannot be considered sustainable practices in aquaculture. Cleaner fish use is preferred if fish health and welfare criteria are met. A lack of data related to warm water treatment was noted, which is a research gap. Keywords: Atlantic salmon, salmon lice, chemical treatment, warm water treatment, cleaner fish